2014
DOI: 10.18632/oncotarget.1848
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the MUC1-C oncoprotein inhibits self-renewal capacity of breast cancer cells

Abstract: The capacity of breast cancer cells to form mammospheres in non-adherent serum-free culture is used as a functional characteristic of the self-renewing stem-like cell population. The present studies demonstrate that silencing expression of the MUC1-C oncoprotein inhibits growth of luminal MCF-7 and HER2-overexpressing SKBR3 breast cancer cells as mammospheres. We also show that triple-negative MDA-MB-468 breast cancer cells are dependent on MUC1-C for growth as mammospheres and tumor xenografts. Similar result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 55 publications
(117 reference statements)
6
78
0
Order By: Relevance
“…EMT also increases the capacity for cells to undergo invasion and to form spheres in non-adherent serum-free culture, which is dependent on the presence of self-renewing stem-like cells (26, 27). Consistent with the induction of ZEB1 and EMT, other work has demonstrated that MUC1-C contributes to the self-renewal of breast and NSCLC stem-like cells (28, 29). Other studies in NSCLC cells harboring EGFR or KRAS mutations have shown that targeting the MUC1-C pathway inhibits their growth as tumors in mice (29, 30).…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…EMT also increases the capacity for cells to undergo invasion and to form spheres in non-adherent serum-free culture, which is dependent on the presence of self-renewing stem-like cells (26, 27). Consistent with the induction of ZEB1 and EMT, other work has demonstrated that MUC1-C contributes to the self-renewal of breast and NSCLC stem-like cells (28, 29). Other studies in NSCLC cells harboring EGFR or KRAS mutations have shown that targeting the MUC1-C pathway inhibits their growth as tumors in mice (29, 30).…”
Section: Introductionsupporting
confidence: 58%
“…Overexpression of MUC1-C has been linked to the induction of EMT, stemness and self-renewal in breast and certain other cancer cells (25, 28). The LIN28B→let-7 pathway has also been shown to confer self-renewal of breast cancer stem-like cells, at least in part through the suppression of HMGA2 (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oncomed has recently initiated phase II clinical trials for tarextumab in patients with pancreatic and/or lung cancer. Genus Oncology is targeting Mucin 1 (MUC-1), an oncoprotein that has a pivotal role in tumor progression in AML, multiple myeloma, colon cancer, non-small cell lung carcinoma and breast cancer [149][150][151][152]. The company has recently moved its drug candidate, GO-203-2c, into phase Ib/IIa clinical development.…”
Section: Establishing Proof-of-concept In Human Studiesmentioning
confidence: 99%